An implicit neural familiar face identity recognition response across widely variable natural views in the human brain. Issue 3 (2nd July 2020) - Yan, Xiaoqian; Zimmermann, Friederike GS; Rossion, Bruno
ABSTRACT: Highly variable natural images of the same familiar face celebrity interleaved periodically in a rapid (6 images/second) train of unfamiliar faces automatically elicit an objective electroencephalographic (EEG) response over the occipito-temporal cortex of neurotypical human adults within a few minutes. However, the extent to which this frequency-tagged response goes beyond the association of common physical features of the periodically repeated face identity remains unknown. Here we compare participants who know or do not know the very same periodically repeated face celebrity and show that long-term familiarity accounts for about 80% of the neural face identity recognition response. This familiarity advantage disappears with upside-down images. Variability in response amplitude between face identities is preserved for inverted faces and in unfamiliar participants, suggesting a contribution of within-person physical face variability and distinctiveness to about 20% of the face identity response. These observations provide the strongest difference to date in human brain response between the same famous face identities perceived as familiar or unfamiliar in an implicit task. The frequency-tagged neural response largely reflects the strengthening effect of long-term memory in the human occipito-temporal cortex, and may serve to index automatic familiar face identity recognition in individual observers.